Foucault's Disagreement with Heidegger and Derrida about Understanding and Interpreting Plato's Philosophy - Seyed Jamal Ghoreyshi Khorasgani; Ali Karbasizade Isfahani (Journal of Philosophical Investigations)
Focusing on Heidegger's and Derrida's interpretations of Plato, this paper highlights a line of interpretation in which Plato is seen as the origin of a philosophical understanding that dismisses the hidden aspect of Being and truth. Against this line, Foucault's interpretation of Plato and Greek philosophical practices is elaborated. Considering this interpretation, it becomes clear that we are dealing with two distinct descriptions of Greek philosophical practices and their relation to the rise of modernity: one that views modernity as an extension of the deepest meanings embedded in Greek metaphysics and another that interprets the foundations of modern philosophy in opposition to the basis of Platonic thought, seeing Plato and the ancient philosophical approaches influenced by him as an avenue for resisting modern domination. Although Foucault's project on the art of living owes much to Heidegger's ideas about care of the self and the work of art, it allows Foucault to offer a different interpretation of Plato. We show the methodological considerations that enable Foucault to present this distinct interpretation. To achieve such an interpretation, Foucault focuses on the practices of writing, logos, and truth as parrhesia in Plato's thought and Greek philosophy. Following Foucault's path, we offer an analysis of forms, Agathon, and dialogue that emphasizes their living, engaging, aesthetic, and political aspects. This conceptual and methodological toolkit helps us to introduce and develop an alternative interpretive line of Plato's thought.